The unraveling of Julia : a psychological thriller - Scottoline, Lisa (New York : Grand Central Publishing, 2025)
After the shocking death of her husband, a troubled young widow inherits a Tuscan estate from a mysterious benefactor and finds herself thrust into the crosshairs of a dangerous conspiracy.
Keywords: Widows -- Fiction; Grief -- Fiction; Fate and fatalism -- Fiction; Blessing and cursing -- Fiction; Survival -- Fiction; Recluses -- Fiction; Families -- Fiction; Astrology -- Fiction; Tuscany (Italy) -- Fiction; Psychological fiction; Thrillers (Fiction)